PROBLEMATIKA PEMBELIAN KEMBALI SAHAM DALAM UU PT DAN UU PASAR MODAL - Tri Budiyono (Faculty of Law, Universitas Diponegoro, 2011)
These studies are tries to compare and analysis of share buyback under the Corporation Act ( Act 40/2007) and Capital Market Act (Act 811995). The results of these studies are they are two kind of share buyback under Corporation Act, voluntary share buyback (under art. 37-40), compulsory share buyback (under art.62). The other variations were found under Capital Market Act. There are tree kinds of share buyback. There are share buyback which specifically used by Mutual Fund, share buyback used by corporation under normal situation, and share buyback used by corporation under crisis situation.